(untitled) (Journal of Contemporary Issues in Accounting, 2023)
Resource management is one of the best Indicators of accountability in financial sector in developing and developed countries of the world. However, resource management and accountability in Nigeria leave a lot of room for improvement because of inefficient and ineffective managerial practices among the key players in financial sectors. Studies have shown that resources management is sine-qua-non for the realization of the accountability in financial sector in Nigeria economy. Hence, the article examines resources management and accountability in the financial sector in Nigeria. The financial sector represented by banks and non-banks financial institutions, which is so crucial to the Nigeria economy in terms of its contribution to national financial stability and economic growth. To appreciate, the role of resources management vis-à-vis the accountability in the financial sector in Nigeria. The paper focuses on efficient and effectiveness of financial resources, inventory, information technology, human skills, economic and natural resources management in some Nigeria bank and non-bank industries and their accountabilities, which burden on the unethical practices of their executives. The study employs descriptive statistics, using questionnaire as instrument of data collection. Data were analyzed using correlation and ordinary least square method. The paper observed that, there is strong positive correlation between resources management and accountability in the financial sector in Nigeria. Also there is a significant positive effects of resources management on fiscal, program, and individual accountability in financial sectors upon this finding recommendation were made.